Corneal laceration caused by river crab - Naidu, Vinuthinee; Anuar, Azreen Redzal; Jaafar, Juanarita; Embong, Zunaina (Dove Medical Press, 2015)
A 5-year-old boy presented with right eye pain associated with tearing and photophobia of 1-day duration. He gave a history of playing with a river crab when suddenly the crab clamped his fingers. He attempted to fling the crab off, but the crab flew and hit his right eye. Ocular examination revealed a right eye corneal ulcer with clumps of fibrin located beneath the corneal ulcer and 1.6 mm level of hypopyon. At presentation, the Seidel test was negative, with a deep anterior chamber. Culture from the corneal scrapping specimen grew Citrobacter diversus and Proteus vulgaris, and the boy was treated with topical gentamicin and ceftazidime eyedrops. Fibrin clumps beneath the corneal ulcer subsequently dislodged, and revealed a full-thickness corneal laceration wound with a positive Seidel test and shallow anterior chamber. The patient underwent emergency corneal toileting and suturing. Postoperatively, he was treated with oral ciprofloxacin 250 mg 12-hourly for 1 week, topical gentamicin, ceftazidime, and dexamethasone eyedrops for 4 weeks. Right eye vision improved to 6/9 and 6/6 with pinhole at the 2-week follow-up following corneal suture removal.